The Influence of Research and Development Activities on Company Growth: Age, Size and Market Share of Companies as Moderators - Frisniari Dwi Widyastuti; Djuminah Djuminah (Budapest International Research and Critics University, 2022)
Industrial competition is currently getting higher and more competitive, especially with the presence of foreign products that characterize the domestic market. On the other hand, the presence of Industry 4.0 which has been echoed since 2011, has made global industry players more competitive to be able to advance their respective technologies based on computer technology and internet networks. Of course, domestic industry players will also not remain silent in the face of this increasingly sharp competitive climate. Supported by the government, in this case the Ministry of Industry, the competitive power of the domestic industry is constantly being honed with various programs being rolled out. One of them is the innovation of superior products as the output of research and development programs that must synergize between the government, the private sector, the community and universities. This study examines whether the research and development activities carried out by the company affect its growth. In the next stage, moderating with age, size and market share is expected to further sharpen this influence.